Comparative evaluation of different DC-AC converter topologies for cryogenic applications utilizing superconducting materials. Issue 1 (1st May 2022) - Ul Hassan, M; Emon, A I; Azadeh, Y; Luo, F
Abstract: Modern transportation applications including electric vehicles (EVs), more electric aircraft (MEA) and electric comprise of different power conversion systems. Reduced weight and improved semiconductor efficiency are the major challenges towards their improved overall performance. To overcome them, cryogenic operation of power electronics converters (CPEC), electric motors, cables, and energy storage components has been under research and evaluation. CPEC are being investigated to drive superconducting machines (SCM) because of their lightweight structure and improved efficiency. CPEC can offer improved switching performance, reduced conduction losses and therefore increased efficiency; because of reduced on-resistance and increased carrier mobility of active devices. This article will discuss how can the benefits of lower operating temperature (< 93 K) be utilized in determining the most suitable DC-AC converter configuration. The paper compares three basic converter topologies: (a) two level voltage source inverter (2L-VSI), (b) three level t-type neutral point clamped inverter (3L-TNPC) and (c) two-level current source inverter (2L-CSI). Analysis is provided based on volume of passive components, electromagnetic interference (EMI) spectra and number of active devices, where all components considered are compatible with low temperatures. It can be observed that utilization of cryogenic temperature affects the volume of passive components, and therefore the overall selection of converter.